Gastrointestinal Bleeding and Direct Oral Anticoagulants among Patients with Atrial Fibrillation: Risk, Prevention, Management, and Quality of Life - Zappulla, Paolo; Calvi, Valeria (TH Open, 2021)
A significant problem for patients undergoing oral anticoagulation therapy is gastrointestinal bleeding (GIB), a problem that has become increasingly urgent following the introduction of direct oral anticoagulants (DOACs). Furthermore, in recent years a greater focus has been placed on the quality of life (QOL) of patients on long-term oral anticoagulant therapy, which necessitates changes in lifestyle, as well as posing an increased risk of bleeding without producing objective symptomatic relief. Here, we examine current evidence linked to GIB associated with oral anticoagulants, with a focus on randomized control trials, meta-analyses, and postmarketing observational studies. Rivaroxaban and dabigatran (especially the 150-mg bis-in-die dose) appeared to be linked to an increased risk of GIB. The risk of GIB was also greater when edoxaban was used, although this was dependent on the dose. Apixaban did not pose a higher risk of GIB in comparison with warfarin. We provided a summary of current knowledge regarding GIB risk factors for individual anticoagulants, prevention strategies that lower the risk of GIB and management of DOAC therapy after a GIB episode.
Keywords: oral anticoagulant; gastrointestinal bleeding; warfarin; rivaroxaban; dabigatran; edoxaban; apixaban